The Power of EI Competencies Over Intelligence and Individual Performance: A Task-Dependent Model - Truninger, Margarida; Fernández-i-Marín, Xavier; Batista-Foguet, Joan M.; Boyatzis, Richard E.; Serlavós, Ricard (Frontiers in Psychology, 2018)
Prior research on emotional intelligence (EI) has highlighted the use of incremental models that assume EI and general intelligence (or g) make independent contributions to performance. Questioning this assumption, we study EI’s moderation power over the relationship between g and individual performance, by designing and testing a task-dependent interaction model. Reconciling divergent findings in previous studies, we propose that whenever social tasks are at stake, g has a greater effect on performance as EI increases. By contrast, in analytic tasks, a compensatory (or negative) interaction is expected, whereby at higher levels of EI, g contributes to performance at a lesser extent. Based on a behavioral approach to EI, using 360-degree assessments of EI competencies, our findings show that EI moderates the effect of g on the classroom performance of 864 MBA business executives. Whilst in analytic tasks g has a stronger effect on performance at lower levels of EI competencies, our data comes short to show a positive interaction of EI and g in affecting performance on social tasks. Contributions and implications to research and practice are discussed.